Gustilo–Anderson Type II to IIIA Transition as a Critical Point in Osteomyelitis Risk Among Open Tibial Fractures - Muhammad Orri Baskoro; Kemal Akbar Suryoadji; Jafri Hasan (CV. CENDIKIA JENIUS INDONESIA, 2026)
Background: Open tibial fractures are severe orthopaedic injuries with a substantial risk of infection, including osteomyelitis, which may complicate treatment and worsen outcomes. Fracture severity is commonly assessed using the Gustilo–Anderson (GA) classification, but its role in stratifying osteomyelitis risk remains incompletely defined. Objective: This study aimed to evaluate osteomyelitis risk stratification based on the Gustilo–Anderson classification in open tibial fractures. Methods: A systematic search of PubMed, the Cochrane Library, and EMBASE was conducted up to February 2026. Studies reporting osteomyelitis incidence in open tibial fractures according to GA classification were included. Data were extracted independently by two reviewers. A network meta-analysis was performed using MetaInsight software, calculating relative risks (RRs) with 95% confidence intervals (CIs), and visualized using SUCRA rankings. Results: Five studies involving 1,134 open tibial fractures were included. Osteomyelitis prevalence ranged from 9.5% to 33%. The risk of osteomyelitis increased with higher GA grades, with a significant increase observed from GA type II to type IIIA (RR 2.86; 95% CI: 1.24–6.60). No significant risk differences were found between GA types I and II or among GA type III subtypes. Conclusion: The transition from GA type II to IIIA represents a critical threshold for osteomyelitis risk in open tibial fractures. Early GA-based classification provides important prognostic value and may guide clinical decision-making for infection prevention